UNGKAPAN EMOSI MASYARAKAT DALAM BAHASA MINANGKABAU DI NAGARI TANJUNG BINGKUNG KECAMATAN KUBUNG KABUPATEN SOLOK - Raman Putra; Novia Juita; Ngusman Ngusman (Jurnal Bahasa dan Sastra, 2013)
This researchdone to describe (1) the form of expression of emotions angry, sad, and happy in the Minangkabau language used in Nagari Tanjung Bingkung Subdistrick Kubung Regency Solok, (2) the context in which the expression of emotion angry, sad, and happy in the Minangkabau language in Nagari Tanjung Bingkung Subdistrick Kubung Regency Solok.This research is a qualitative study using descriptive methods. Object of this study is the expression of emotion in the language of Minangkabau Society inNagari Tanjung Bingkung Subdistrick Kubung Regency Solok. Analyzed data taken with the following steps: (1) transcribe data from various sources into written language, that is, from the recorded data, interviews, and observations, (2) inventaritation shape emotional expression and context, (3) classify forms of emotional expression and context, (4) analyzing the data collected, and (5) formulating the research findings. Based on these results, it is concluded that there are three expressions of emotion in the Minangkabau language in Nagari Tanjung Bingkung Subdistrick Kubung Regency Solok, namely: (1) there are 41 angry expressions of emotion expression, (2) there are 37 sad emotion expressions, (3) the expression of emotion happy there are 30 expressions. (a) The speaker ofthe old manto the young menathomeandin the shoptend touse the expression ofthe emotion of angry, anjiang example; sad emotional expressions panduto example, ibo; happy emotional expression example bauntuang, (b) young male speakers toold menathomeandin the shoptendto use the expression of emotion angry batele, tenggen example; sad emotional expression example ibo; happy emotional expression cadiak example, (c) male speakers to male a geathomeandin the fieldtend touse angry emotional expression example pantek andekang; expression of emotion sad example ndak disangko; happy emotional expression example sanangnyo, (d) older women speakers to the young women at home and in the shoptends tousel esssample wrote angry emotions; sad emotional expression exampl epadiah; expression happy emotion barasaki example, (e) young women speakers to the old woman in the house and in the shoptend touse the expression of emotion angry kalera example; expression of emotion sad example basalahan; emotion excited expression baruntuang example, (f) to women age women speakers at home and installstendto use examples ofnervousemotion of anger; sad emotional expressions are not encounteredin the study investigators; expression of emotion excited sanang example.